Fragile X Syndrome in China - Duan, PhD, Ranhui; Garber, PhD, Kathryn; Jin, Peng (North American Journal of Medicine and Science, 2013)
Fragile X syndrome (FXS) is the most common form of inherited intellectual disability (ID), and the leading monogenic cause of autism spectrum disorders. The FXS cases in China were first reported in 1984, and effort has been made to improve the wellbeing of FXS patients. However, the general Chinese population is unfamiliar with FXS due to the limited public education. Even among those with medical training, there is a lack of awareness. Here our review aims to provide basic information on FXS, introduce the clinical aspects of FXS in China, and outline future research and policy recommendations that may in the future improve FXS genetic testing and counselor training in the Chinese health system. [N A J Med Sci. 2013;6(4):181-185. DOI: 10.7156/najms.2013.0604181]